2011
DOI: 10.5951/jresematheduc.42.2.0127
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Learned by Young Children in an Intervention Based on Learning Trajectories: A Large-Scale Cluster Randomized Trial

Abstract: This study employed a cluster randomized trial design to evaluate the effectiveness of a research-based intervention for improving the mathematics education of very young children. This intervention includes the Building Blocks mathematics curriculum, which is structured in research-based learning trajectories, and congruous professional development emphasizing teaching for understanding via learning trajectories and technology. A total of 42 schools serving low-resource communities were randomly selected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(137 citation statements)
references
References 59 publications
6
131
0
Order By: Relevance
“…These findings expand previous results showing that early number skills can be supported effectively through targeted interventions (e.g., Baroody et al, 2009; Clements, Sarama, Spitler, Lange, & Wolfe, 2011; Dyson et al, 2013; Jordan, Glutting, Dyson, Hassinger-Das, & Irwin, 2012). Designed specifically for children who come to kindergarten behind their peers, the present intervention began with the smallest counting numbers and used those numbers to reinforce verbal subitizing, counting and cardinality, magnitude comparisons, and adding and subtracting (Clements et al, 2013; Frye et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…These findings expand previous results showing that early number skills can be supported effectively through targeted interventions (e.g., Baroody et al, 2009; Clements, Sarama, Spitler, Lange, & Wolfe, 2011; Dyson et al, 2013; Jordan, Glutting, Dyson, Hassinger-Das, & Irwin, 2012). Designed specifically for children who come to kindergarten behind their peers, the present intervention began with the smallest counting numbers and used those numbers to reinforce verbal subitizing, counting and cardinality, magnitude comparisons, and adding and subtracting (Clements et al, 2013; Frye et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Sarama and colleagues (2012) made a similar argument, observing that sets of literacy and mathematics skills are learned at similar times and that one set of skills reinforces the other. Previous research has focused on investigating which academic domain, mathematics or literacy, might be most beneficial for academic development and this has led to conflicting evidence (Duncan et al, 2007; Clements et al, 2011; Sarama et al, 2012; Clements & Sarama, 2011; Purpura et al, 2011; Morgan et al, 2015). Based on the results of the current study, it appears that promoting either resilience in mathematics or literacy among children in poverty could lead to positive growth in both within-domain and cross-domain academic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In analyses using six longitudinal data sets the level of early mathematics skills was the strongest predictor of both later mathematics and reading achievement (Duncan et al, 2007). Other studies have demonstrated that early math curricula interventions are related to improvements in mathematics but also to gains in language and literacy skills (Clements, Sarama, Spitler, Lange, & Wolfe, 2011; Sarama et al, 2012; Clements & Sarama, 2011). Resilience might vary across different domains of development, however, we would expect that children who do well on one domain will also do well on theoretically similar domains of development (Luthar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This model of teaching and learning, or “learning and teaching” (Clements & Sarama, 2004, p. 81), gives attention to the interplay between teachers, the curriculum, and the learners that allows some freedom for movement within the instructional activities. Past research has shown that this model of instruction (student-led as opposed to teacher-directed) produces desired change when used with typical learners (Clements, Sarama, Spitler, Lange, & Wolfe, 2011; Szilágyi, Clements, & Sarama, 2013). Socially mediated instruction, however, has been found to be less effective than direct instruction models for teaching students with LD, although these findings have been based on far more research conducted on the teaching of basic skills (where direct instruction makes sense), than on mathematical problem solving (Kroesbergen & VanLuit, 2003).…”
Section: Step 2: Delineation Of Intervention’s Componentsmentioning
confidence: 99%